Enhanced the Performance of Digital Image Compression Using Wavelet Transform Function and BP Neural Network Model - Yadav, JS; Dhariwal, S (International Journal of Computer Sciences and Engineering, 2025)
The compression technique play vital role in digital multimedia data. The size of digital multi-media is very high due to this reason used more memory space for storage and need more bandwidth for transmission of data. the data compression techniques used various approaches like pixel based methods and some are transform based method. In the research work introduced better approach for picture pixel size reduction. The approach is addition of WT and BPN model. The BPNN model is very efficient model in terms of processing of data of WT function. The proposed algorithm implemented in MATLAB and used reputed image for compression. Our empirical result shows better PSNR and C.R instead of Wavelet transform method.